Revisiting the framework of the National Institute on Aging‐Alzheimer's Association diagnostic criteria. Issue 5 (1st September 2013) - Carrillo, Maria C.; Dean, Robert A.; Nicolas, François; Miller, David S.; Berman, Robert; Khachaturian, Zaven; Bain, Lisa J.; Schindler, Rachel; Knopman, David
Abstract: In 2011, the National Institute on Aging and the Alzheimer's Association (NIA‐AA) proposed revising the criteria for diagnosing Alzheimer's disease (AD), which had been established more than 25 years earlier by the National Institute on Neurologic and Communicative Disorders and Stroke (NINCDS) and the Alzheimer's Disease and Related Disorders Association (ADRDA), now called the Alzheimer's Association. The NIA‐AA initiative also built upon research criteria for AD proposed by the International Working Group (IWG) in 2007 and updated in 2010. These efforts to revise the criteria reflect the need to improve diagnostic accuracy, facilitate clinical trials, and establish a common set of criteria that are universally accepted across domains of clinical practice, research, and drug development. To ensure that the proposed NIA‐AA criteria remain as current as possible, the Alzheimer's Association Research Roundtable convened a meeting in Washington, DC, on October 1 and 2, 2012, bringing together international stakeholders from industry, academia, and regulatory agencies to identify areas of agreement and research gaps respective of NIA‐AA criteria and IWG recommendations.